Influence of nitrogen level and plant density on growth parameters and economic efficiency of sunflower cultured in Thua Thien Hue province - Truong, Hai Thi Hong; Phan, Thao Thu (Hue University Journal of Science: Natural Science, 2022)
Sunflower (Helianthus annuus) cultivation is gaining popularity among Vietnamese farmers. Two separate experiments were conducted from January to April 2018 in a randomized complete block design with three replicates. Four levels of each factor were included in the experiments: 0, 20, 40, and 60 kg/ha for nitrogen and 11, 13, 16, and 20 plants/m2 for the density. The nitrogen fertilizer (up to 60 kg/ha) substantially affects the leaf area, diameters of stem plant, receptacle and flower head, and cut flower vase life. Low plant density works well on plant height, leaf number, width and length at the flowering stage, with the largest head diameter (17.2 cm) at the 13 plants/m2 density. Based on the results of both growth ability and economic efficiency, we suggested applying N at 60 kg/ha and planting at 16 plants/m2 density for growing F1 cut sunflowers in Thua Thien Hue province.